Genetic Association Between Alzheimer’s Disease Risk Variant of the PICALM Gene and EEG Functional Connectivity in Non-demented Adults - Ponomareva, Natalya; Andreeva, Tatiana; Protasova, Maria; Konovalov, Rodion; Krotenkova, Marina; Malina, Daria; Mitrofanov, Andrey; Fokin, Vitaly; Illarioshkin, Sergey; Rogaev, Evgeny (Frontiers in Neuroscience, 2020)
Genome wide association studies (GWAS) have identified and validated the association of the PICALM genotype with Alzheimer’s disease (AD). The PICALM rs3851179 A allele is thought to have a protective effect, whereas the G allele appears to confer risk for AD. The influence of the PICALM genotype on brain functional connectivity in non-demented subjects remains largely unknown. We examined the association of the PICALM rs3851179 genotype with the characteristics of lagged linear connectivity (LLC) of resting EEG sources in 101 non-demented adults younger than 60 years of age. The EEG analysis was performed using exact low-resolution brain electromagnetic tomography (eLORETA) freeware (Pascual-Marqui, 2011). We found that the carriers of the A PICALM allele (PICALM AA and AG genotypes) had higher widespread interhemispheric LLC of alpha sources compared to the carriers of the GG PICALM allele. An exploratory correlation analysis showed a moderate positive association between the alpha LLC interhemispheric characteristics and the corpus callosum size and between the alpha interhemispheric LLC characteristics and the Luria word memory scores. These results suggest that the PICALM rs3851179 A allele provides protection against cognitive decline by facilitating neurophysiological reserve capacities in non-demented adults. In contrast, lower functional connectivity in carriers of the AD risk variant, PICALM GG, suggests early functional alterations in alpha rhythm networks.